Nonoperative Management of the Infected Diabetic Foot - Buckley, Rita (MD Conference Express, 2012)
Diabetes affects 25.8 million people of all ages, or 8.3% of the US population. In 2007, it was the seventh leading cause of death. More than 60% of nontraumatic lower limb amputations occur in people with diabetes. In 2006, that number totaled approximately 65,700 [National Diabetes Information Clearinghouse (NDIC) National Diabetes Fact Sheet 2011]. This article discusses nonoperative management of the infected diabetic foot.